2017
DOI: 10.1007/s00268-017-4296-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome, Social Impact and Patient Expectation: a Purposive Sampling Pilot Evaluation of Patients in Benin Seven Years After Surgery

Abstract: In conclusion, our pilot study shows that NGO surgery in Benin provided positive social impact associated with complication rates comparable to high-income countries when assessed seven years later. Key areas for further study in LMICs are: evaluation and treatment of chronic pain, consent and access to further care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 55 publications
0
18
1
1
Order By: Relevance
“…The follow-up rate at 12–18 months in our longitudinal study was 37% (158/427 originally trained), compared with 47% (183/427) at 4 months 26. This is higher than other LMIC surgical evaluation studies that have reported follow-up rates of 17%–44%40–48 and slightly lower than response rates of 38%–70% for surveys and self-reporting studies in high-income countries 49 50. LMICs studies generally have lower follow-up rates than high-income countries due to challenges such as non-functioning telephone numbers and email addresses, inadequate record-keeping, transport costs and difficulties accessing rural locations.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The follow-up rate at 12–18 months in our longitudinal study was 37% (158/427 originally trained), compared with 47% (183/427) at 4 months 26. This is higher than other LMIC surgical evaluation studies that have reported follow-up rates of 17%–44%40–48 and slightly lower than response rates of 38%–70% for surveys and self-reporting studies in high-income countries 49 50. LMICs studies generally have lower follow-up rates than high-income countries due to challenges such as non-functioning telephone numbers and email addresses, inadequate record-keeping, transport costs and difficulties accessing rural locations.…”
Section: Discussioncontrasting
confidence: 59%
“…Only two-thirds of the original hospital sites were visited and even though no hospital had received further checklist training in the interim, there may have been other factors in the interim that effected operating room procedures, practice and culture outside of our control or knowledge. Follow-up rate from the original training sample of 427 participants was only 37%, but this is comparable to surgical outcome studies in LMICs 40–48. We are unable to contextualise this further because we do not know what per cent of the total surgical staff this represents.…”
Section: Discussionmentioning
confidence: 77%
“…The outcomes reporting in these studies is largely intraoperative morbidity/mortality, immediate postoperative morbidity (within 2–3 days), and rarely 30-day morbidity, with follow-up rates around 20%–30%. An exception is the work of White et al ,16 who reported 7-year follow-up of morbidity, social impact and patient experiences of humanitarian mission surgery (maxillofacial, plastics and orthopaedic) using semistructured interviews and questionnaires. Of 174 patients identified via purposive sampling, 41% participated in the evaluation, and the results included 35% with persistent postoperative pain and 18% who had sought follow-up for a clinical complication.…”
Section: Current Climate Of Outcomes Reporting In Global Surgerymentioning
confidence: 99%
“…Therefore, the current study has selected 10 experts who have great knowledge and more than 15 years of experience in boiler operation in various RMG companies based on the purposive sampling method. Purposive sampling method is used when to select respondents from a specific domain of interest ( White et al., 2018 ). These 10 experts were chosen for having knowledge in the boiler technology domain.…”
Section: Methodsmentioning
confidence: 99%